Stability of Y/MCM-48 composite molecular sieve with mesoporous and microporous structures - Qian Zhao (Journal of Asian Ceramic Societies, 2014)
Y/MCM-48 composite molecular sieve was hydrothermally synthesized at different crystallization temperatures and crystallization times using ethyl orthosilicate as Si source and cetyltrimethyl ammonium bromide as template with the aid of fluoride ions and was characterized by X-ray diffraction, N2 physical adsorption technique, scanning electron microscopy and transmission electron microscopy. The thermal, hydrothermal, acidic, and basic stabilities of the Y/MCM-48 composite were investigated. The results show that Y/MCM-48 composite molecular sieve with meso- and microporous structures was synthesized successfully at 120 °C for 36 h. The Y/MCM-48 composite has the surface area of 864 m2/g and the average pore size is ca. 2.48 nm. The bi-porous structure in composite molecular sieve still maintains its stability even after thermal treatment at 800 °C for 4 h or hydrothermal treatment at 100 °C for 48 h. After treatment in 1 mol/L hydrochloric acid solution or 1 mol/L sodium hydroxide solution for 48 h, the Y/MCM-48 composite exhibits good acidic stability. The acidic stability is superior to the basic stability at the same treatment time.